Effects of some interferon-related proteins on influenza a viruse RNA polymerase activity - TURAN, KADİR (My University, 2022)
© 2022, Turkish Pharmacists Association. All rights reserved.Objectives: Interferons (IFNs) are one of the most important components of innate immunity against viruses, especially those carrying the RNA genomes such as influenza viruses. Upon viral infection, the IFNs are rapidly secreted, inducing the expression of several genes in the target cells and establishing an antiviral state. In this study, the effects of proteins encoded by some IFN-related genes on influenza A virus RNA-dependent RNA polymerase enzyme were investigated. We evaluated the importance of these proteins in the pathogenesis of different influenza A virus types. Materials and Methods: The IFN-related genes were amplified by polymerase chain reaction from the HEK293 cDNA library and cloned into pCHA expression vector. The expression of genes and subcellular localizations of the proteins were determined by Western blotting and immunofluorescence staining, respectively. The effects of IFNs-related proteins on virus RdRP enzyme were determined by influenza A virus mini-replicons. Results: The study revealed that the influenza A virus infections significantly altered the transcript level of the IFN-related CCL5, IFIT1, IFIT3, IFITM3, and OAS1 genes in HEK293 cells. It was determined that the alteration of the gene expression was also related to the virus type. The mini-replicon assays showed that the transient expression of CCL5, IFI27, OAS1, IFITM3, IFIT1, and IFIT3 have inhibitory effects on WSN and/or DkPen type virus RdRP enzymes. We observed that the proteins except OAS1 inhibited WSN type RdRP enzyme at a higher level than that of DkPen enzyme. Conclusion: It was concluded that influenza A virus infection significantly alters the IFN-related gene expression in the cells. Most of the proteins encoded from these genes showed an inhibitory effect on the virus RdRP enzymes in the HEK293 cells. The inhibition of the influenza virus RdRP with IFN-related proteins may be the result of direct or indirect interactions between the host proteins and the viral enzyme subunits.
Keywords: Tıp; Yaşam Bilimleri; Biyoteknoloji; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Biotechnology; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Mikrobiyoloji; TROPİKAL TIP; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MICROBIOLOGY; TROPICAL MEDICINE; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Moleküler Tıp; Farmasötik bilim; Molecular Medicine; Pharmaceutical Science; Influenza A virus interferon response; influenza RdRP; PCR array